1)x²-3x-4>0 x1+x2=3 U x1*x2=-4⇒x1=-1 U x2=4 x∈(-∞;-1) U (4;∞) 2)-x²-3x+4≤0 x²+3x-4≥0 x1+x2=-3 U x1*x2=-4⇒x1=-4 U x2=1 x∈(-∞;-4] U [1;∞) 3)x²+7x+10>0 x1+x2=-7 U x1*x2=10⇒x1=-5 U x2=-2 x∈(-∞;-5) U (-2;∞) 4)-x²+3x-2≥0 x²-3x+2≤0 x1+x2=3 U x1*x2=2⇒x1=1 U x2=2 x∈[1;2]
x1+x2=3 U x1*x2=-4⇒x1=-1 U x2=4
x∈(-∞;-1) U (4;∞)
2)-x²-3x+4≤0
x²+3x-4≥0
x1+x2=-3 U x1*x2=-4⇒x1=-4 U x2=1
x∈(-∞;-4] U [1;∞)
3)x²+7x+10>0
x1+x2=-7 U x1*x2=10⇒x1=-5 U x2=-2
x∈(-∞;-5) U (-2;∞)
4)-x²+3x-2≥0
x²-3x+2≤0
x1+x2=3 U x1*x2=2⇒x1=1 U x2=2
x∈[1;2]